2018
DOI: 10.1002/jcp.26522
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the role of mitochondrial fusion and fission in cardiomyocyte apoptosis induced by ischemia/reperfusion

Abstract: As the main source of energy in the body, mitochondria are highly dynamic organelles, which are constantly going through fusion and fission. The fine balance of mitochondrial fusion and fission plays an important role in maintaining the stability of cardiomyocyte homeostasis. The processes of mitochondrial fusion and fission are very complex, which is mediated by fusion and fission proteins. Disruptions in these processes through controlling fusion and fission proteins affect mitochondrial functions and cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 87 publications
(190 reference statements)
1
35
0
Order By: Relevance
“…e previous study of our Journal of Analytical Methods in Chemistry increase the expression of Bcl2 could exhibit neuroprotection against OGD/R injury [26]. Yu also observed this phenomenon in cardiomyocytes [27].…”
Section: Discussionmentioning
confidence: 65%
“…e previous study of our Journal of Analytical Methods in Chemistry increase the expression of Bcl2 could exhibit neuroprotection against OGD/R injury [26]. Yu also observed this phenomenon in cardiomyocytes [27].…”
Section: Discussionmentioning
confidence: 65%
“…During apoptosis, mitochondria undergo extensive fragmentation, which precedes caspase activation, to release proapoptotic factors [ 36 ]. Excessive fission or decreased fusion contributes to cell apoptosis, while inhibition of mitochondrial fission blocks or delays cell death [ 37 40 ]. The GAS-mediated protection of mitochondria from fragmentation might contribute to the decrease in apoptosis in H 2 O 2 -treated H9c2 cells that were pretreated with GAS.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria reportedly play an important role in the development of I/R injury, which is involved in calcium homeostasis, oxidative phosphorylation, reactive oxygen species production, and apoptosis [13]. Recent studies have suggested that morphological changes in the mitochondria are relevant to I/R injury [8,22,23]. In stress, the balance of mitochondrial fission and fusion is lost, and fission prevails, which promotes fragmented mitochondria and induces mitochondrial dysfunction [2426].…”
Section: Discussionmentioning
confidence: 99%